Radiological risk from thoron, a case study: The particularly radon-prone area of Bolsena, and the lesson learned. (November 2015) - Cinelli, G.; Capaccioni, B.; Hernández-Ceballos, M.A.; Mostacci, D.; Perghem, A.; Tositti, L.
Abstract: The contribution of 220 Rn is usually negligible compared to that of 222 Rn: its very short half-life makes escape from its source site within the rock very unlikely and it never has time enough to filtrate through the ground and through cracks in the floors or cellar walls to reach living quarters. This however becomes untrue if walls built with 232 Th-rich materials are present: then sizeable amounts of thoron may be detected in the closed areas bounded by those walls. This is the case for many dwellings in central Italy, and the town of Bolsena (northern Latium) is presented as a case study. A typical building of the area, entirely constructed with tuff blocks, is investigated and the annual dose rates calculated for varying distances from the wall. Thoron concentration was found to decrease with a relaxation length of 13 cm. Thoron was found to pose a significant risk. The rate of air exchange was found to produce little effect. Wall plastering acts as a filter: thoron diffuses through it but a HVL of less than 1 cm was found to prevail. Highlights: 232Th-rich materials, case study: town of Bolsena (Italy) entirely built with tuff Thoron concentration was found to decrease with a relaxation length of 13 cm. The rate of air exchange is irrelevant: ventilation cannot ensure thoron mitigation. Wall plaster (HVL of 0.95 cm) can contribute efficiently to thoron mitigation.